Strategi Efektif untuk Mengembangkan Instrumen Asesmen Kognitif dalam Pembelajaran Bahasa Indonesia - Ledya Guska Dewi (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
This research aims to develop and implement cognitive assessment instruments in Indonesian language education, with a focus on improving students' high-level thinking abilities. The validity and reliability of this instrument were tested through a series of tests in various schools. The research results show that this instrument is effective in measuring students' abilities in analysis, synthesis and evaluation. The use of technology in assessment instruments increases the efficiency of the evaluation process, although challenges related to technology infrastructure in some schools require special attention. Feedback from students indicated that the instrument was perceived as relevant and motivating, supporting the importance of authentic assessment practices. Overall, this research emphasizes the importance of a collaborative and comprehensive approach in improving students' learning and their preparation for future demands.